Satellite-based measurement-device-independent quantum key distribution - Wentao Liang; Rongzhen Jiao (New Journal of Physics, 2020)
A satellite-based measurement-device-independent quantum key distribution model is proposed and its performance is analyzed through numerical simulations. The simulation result shows that the key rate increases almost linearly as transmittance increases and the higher the key rate is, the lower its probability may be. More significantly, as the transmission distance increases, the optimal intensities of the signal states decrease while those of the decoy states increase. The optimal values in the daytime are slightly larger than those at night. This work may provide some important parameters for the relevant experiment on satellite-based quantum communication network.